SOCIAL CAPITAL AND LIVELIHOOD DIVERSIFICATION: TOURISM ENTREPRENEURSHIP IN A REMOTE AREA OF NORTH HALMAHERA, INDONESIA - Yerik Afrianto Singgalen; Gatot Sasongko; Pamerdi Giri Wiloso (Universitas Gadjah Mada, 2019)
This article aims to describe the capability of public access to social capital as a form of livelihood diversification through tourism entrepreneurship. This idea was originated from the optimization of the tourism sector and the creative economy by the local government since 2017, aiming to encourage creative entrepreneurship in tourism, creative multimedia, and coffee shop businesses. This study was conducted in a qualitative approach; thus, primary and secondary data sources were used to analyze the data. The primary data was obtained through in-depth interviews and observations, while the secondary data was obtained from document studies. In this case, the in-depth interviews were conducted with the entrepreneurs. The participants involved as key informants had various backgrounds in tourism entrepreneurship such as travel agent and tour guide service, creative multimedia service, and coffee shop business. Furthermore, field observations were done based on activities or events, aiming to observe the process of involvement of these entrepreneurs in regional tourism activities during the events of “Torang Angkat Sampah” in 2017, “Tanjung Bongo Festival” in 2017, “North Galela Festival” in 2018, “Wonderful North Halmahera” in 2018, and “O Molulu Ma Akere” in 2019. The secondary data used was the Medium Term Program Plan of the Local Government Agencies of the Regional Tourism Department of North Halmahera Regency after there was a policy of creative economy development elaborated in the bureaucratic structure changes at the Regional Tourism Department. The results show that the availability of infrastructure, accessibility of information and transportation, and the capability of access to social capital were such a stimulus for the diversification of people’s livelihoods to run tourism, creative multimedia, and coffee shop businesses. Through social capital, entrepreneurs were strengthened by their social relations with various communities to have more consumers while also maintaining the business sustainability.